Heat transfer in the thermal entry region of singly-connected tubes with uniform wall temperature - Canhoto, Paulo (2012)
In this work we address the problem of laminar flow characteristics in the thermal entry region of single-connected circular tubes with uniform wall temperature. The velocity profile is considered to be fully developed and the thermal and transport properties of the fluid are assumed to be constant. By invoking the heat transfer and fluid flow similarity solutions for the case of a flat plate, from analogy between heat and momentum transfer a new relation was established and compared with the Graetz and Lévêque solutions for the thermally developing region in circular tubes. An asymptotic method is used to obtain the overall Nusselt number in the entire range of the dimensionless thermal length of the flow. Results are compared with da-ta and a very good agreement is observed.